Alternative futures for changing landscapes : - Steinitz, Carl (Island Press, 2003)
The book describes how the research team, working with local stakeholders, developed a set of scenarios which encompassed public opinion on the major issues facing the area. They then simulated an array of possible patterns of land uses and assessed the resultant impacts on biodiversity and related environmental factors including vegetation, hydrology, and visual preference